PERUBAHAN SIFAT KIMIA SMART FLAVOR BERBAHAN IKAN BIBISAN SELAMA PENYIMPANAN DAN ANALISIS EKONOMINYA - Belgis, Maria; Witono, Yuli; Nuraini, Aisyah; Nafi’, Ahmad (Jurnal Penelitian Sains dan Teknologi Indonesia, 2022)
Smart flavor is a food flavor generator made from cardinal fish which has a high content of antioxidants and protein. The research objective was to determine changes in critical water content, antioxidant activity, dissolved protein during storage and to analyze the economy and nutrition. This research used two observation variables, namely the difference in temperature (cold and room) and storage time (4 days). The results showed a decrease in critical water content, antioxidant activity, and dissolved protein for 4 days of storage at room and cold temperature. The critical moisture content at room temperature storage is 8,65-9,37% and at cold temperature storage is 7,46-8,22%. Changes in antioxidant activity at room temperature storage were 72,56-41,35% and in cold temperature storage were 75,94-41,35%. The changes in dissolved protein at room temperature storage were 5,151-2,958µg and at cold storage were 5,211-4,377µg. Economic analysis shows that the cost of goods manufactured is Rp 2.581 , BEP units 52792 , BEP rupiahs of Rp 204.393.223 , NPV of Rp 672.228.848 , net B/C of Rp 1.5 , PBP of 0,15 years.